DETERMINAN AGING POPULATION DI 5 NEGARA BERKEMBANG DI WILAYAH ASEAN: PENDEKATAN DATA PANEL - Jati Sukoco, Tri Wahyu Danang; Marpaung, Grace Natalia (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.04.TAHUN.2025, 2025)
The rapid increase in the elderly population presents a significant challenge in many developing countries, including ASEAN members. This study investigates the factors influencing population aging in Indonesia, Malaysia, the Myanmar, Thailand, and Vietnam over the period of 2000 to 2023. Employing a Fixed Effects Model (FEM), this research examines the relationship between the proportion of the elderly population and the independent variables: fertility rate, life expectancy, Human Development Index (HDI), and female labor force participation rate. The analysis reveals that fertility rate and female labor force participation rate exhibit a statistically significant negative relationship with the proportion of the elderly population. Conversely, life expectancy and HDI demonstrate a statistically significant positive influence on the proportion of the elderly population. These findings highlight the importance of policies that consider trends in fertility, improvements in healthcare and longevity, advancements in human development, and the evolving role of women in the workforce when addressing the implications of population aging in the region. In response to this demographic shift, ASEAN countries should prioritize comprehensive strategies encompassing social security reforms, enhanced elderly care systems, initiatives for workforce adaptation, and policies that support sustainable human development.